PENERAPAN MODEL PEMBELAJARAN KOOPERATIFTIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVB SD NEGERI 163 PEKANBARU - Alpusari, Mahmud Alpusari; ', Nora; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This research is motivatedbylow yieldssocial studiesstudents, withthe averagegrade61.14. While the value ofCompleteMinimalCriteria(KKM) is70.AmongIPSstudentsnumbering35people only10 studentswhoreachedthe KKMwithclassical completeness28.57. Data collection instrumentsinthis thesisis asheetactivities of teachersand students andlearning outcomes. with an average of61.14increasein the first cyclewith theaverage being67.43comparedwith a base scoreincreased10.28%. In the second cycleincreased to70.57with an increaseof 15.42%. CycleIIIan increase inaveragestudent learning outcomesform the76.57with an increase of25.23%. the first cycle ofthe first meeting ofthe percentage ofthe activity ofcategoricalenoughteachers56.25%, an increasein thesecond meetingsisklusI withthe percentage59.38% categorizedenough. At thefirstmeeting ofthe second cyclealso increasedwiththe percentage of68.75% categorizedwell, alsoatthe second meeting ofthe secondcycle ofincreasedactivitywith the percentage of71.88% categorizedeither. At thefirst meeting of thethird cycleactivityalso increasedthe percentageof teacherswithan excellent84.38% category, alsoatthe second meeting ofthe third cycleincreasedwiththe percentage of90.63% categorizedvery well. The results ofthe data analysisof student activityin the first cyclethe first meetingof student activitypercentage50.00% lesscategory, has increased in thesecond meetingsisklusI with56.25% percentagecategorizedenough. At thefirstmeeting ofthe second cyclealso increasedwiththe percentage of65.63% categorizedwell, alsoatthe second meeting ofthe secondcycle ofincreasedactivitywith the percentage of71.88% categorizedeither. At thefirst meeting of thethird cyclealso increasedactivitywiththe percentage of81.25% of studentscategorizedvery well, alsoatthe second meeting ofthe third cycleincreasedwiththe percentage of87.50%categorizedvery well. The results ofthe studyinclassIVSDN163Pekanbaruprovethat the implementation ofcooperative learning model typeGroup Investigationcanimprove learning outcomesIPS163fourth grade studentsof SDNPekanbaru. Keywords: Cooperatif type group investigation, IPS Learning Outcomes